2016
DOI: 10.1111/ner.12376
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Vagus Nerve Stimulation Triggered by Ictal Tachycardia: Clinical Outcomes and Device Performance—The U.S. E-37 Trial

Abstract: ObjectivesThe Automatic Stimulation Mode (AutoStim) feature of the Model 106 Vagus Nerve Stimulation (VNS) Therapy System stimulates the left vagus nerve on detecting tachycardia. This study evaluates performance, safety of the AutoStim feature during a 3‐5‐day Epilepsy Monitoring Unit (EMU) stay and long‐ term clinical outcomes of the device stimulating in all modes.Materials and MethodsThe E‐37 protocol (NCT01846741) was a prospective, unblinded, U.S. multisite study of the AspireSR® in subjects with drug‐re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(81 citation statements)
references
References 24 publications
(30 reference statements)
1
80
0
Order By: Relevance
“…Short-term evaluation of 20 patients in the epilepsy monitoring unit after implantation showed that almost 35% of 89 seizures were treated by the responsive stimulation and 61% of them terminated. In the long term, the responder rate after 12 months was 50% and the adverse effects were similar to the previous VNS devices 16 . In another published prospective and multicenter study, short-term evaluation demonstrated that 40% of seizures were treated by closed-loop stimulation and 58% of them ended.…”
supporting
confidence: 59%
“…Short-term evaluation of 20 patients in the epilepsy monitoring unit after implantation showed that almost 35% of 89 seizures were treated by the responsive stimulation and 61% of them terminated. In the long term, the responder rate after 12 months was 50% and the adverse effects were similar to the previous VNS devices 16 . In another published prospective and multicenter study, short-term evaluation demonstrated that 40% of seizures were treated by closed-loop stimulation and 58% of them ended.…”
supporting
confidence: 59%
“…Due to the autostimulation and better seizure control, it is possible to prolong the OFF‐time, which leads to significantly reduced power usage. The initiation of AutoStim itself does not seem to increase power usage prominently . The normal mode stimulation cycle was prolonged in ten patients, only one of them being a responder; in three out of four (75%) responders, the duty cycle remained unaltered.…”
Section: Discussionmentioning
confidence: 84%
“…At present, there is a lack of data concerning the long‐term effect of VNS with AutoStim features. In one study with 20 VNS patients with a one‐year follow‐up, AutoStim and the extra stimulations did not significantly affect power usage, since the measured duty cycles increased from a baseline of 11% with stimulation to about 16% when Normal Mode, AutoStim, and Magned Mode were combined, all on at six months . The majority, 74%, of focal impaired awareness seizures (FIAS) and focal to bilateral tonic clonic seizures (FBTCS) evoked at least a 20% increase in the heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the evidence for benefit of rapid cycling of VNS is limited. The latest generation of stimulator can deliver stimulation in response to a preprogrammed degree of ictal tachycardia, thereby providing a type of responsive rapid cycling [11,12].When optimal stimulation parameters and the mechanisms underlying them are unknown, controlled experiments in a laboratory can be useful, and such an experiment is provided by the article by Larsen et al [13] in this issue, entitled BVagus nerve stimulation applied with a rapid cycle has more profound influence on hippocampal electrophysiology than standard cycle.T he investigators implanted stimulating electrodes in rat perforant path (PP), which is afferent to dentate gyrus of hippocampus, and recording field [electroencephalography (EEG)] electrodes in dentate gyrus. Spontaneous dentate EEG and EEG evoked by PP stimulation were studied under different conditions of vagus nerve activation.…”
mentioning
confidence: 99%
“…Therefore, the evidence for benefit of rapid cycling of VNS is limited. The latest generation of stimulator can deliver stimulation in response to a preprogrammed degree of ictal tachycardia, thereby providing a type of responsive rapid cycling [11,12].…”
mentioning
confidence: 99%